College graduates’ perceptions of their use of teamwork skills: soft skill development in Fort Hays State University Leadership Education - Brungardt, Christie J. (Kansas State University, 2009)
As the world has changed over the last century, so has the world of work. Today’s knowledge workers have fewer individual repetitive tasks, more autonomy, and more need to work with and through people at every level of an organization (Overtoom, 2000). As a result of the ‘flattening’ of the organizational hierarchy, it is critical that employees at all levels are proficient in soft skills. Recent studies indicate that employers consistently rate these skills as deficient in their incoming hires. Skills such as communication, teamwork, leadership and adaptability are commonly ranked as deficient. Academic leadership education strongly emphasizes this valuable skill set often referred to as soft skills. This study examined the relationship of the soft skills gained to the amount of leadership education completed by Fort Hays State University graduates using the Teamwork Skills Questionnaire (O’Neil, Lee, Wang & Mulkey, 1999). Those who received no leadership education from the FHSU Department of Leadership Studies were compared with those who received a leadership certificate and those who received a bachelor’s degree in Organizational Leadership. The study provided insight into whether academic leadership education enhances graduate’s soft skill development and to assess the impact this has on their perception of teamwork proficiency in the workplace. Results indicate that the leadership certificate does not significantly change soft skill development in graduates’ self-reported perceptions, as compared to students with no leadership coursework. It was found that the bachelor’s degree does make limited significant changes in graduates’ soft skill proficiency as compared with graduates who received the leadership certificate. Multiple significant changes were found in graduates with bachelor’s degrees as compared with graduates who received no leadership coursework. Recommendations to be considered when conducting further research include the use of qualitative methodology, the inclusion of more universities that offer a degree in Organizational Leadership, and the measurement of other skills the leadership coursework may produce but was not reflected in this instrument.
Keywords: Soft skills; Teamwork skills; Leadership education; College graduates; Education, Higher (0745)